One input voltage and three output voltage universal biquad filters with orthogonal tune of frequency and bandwidth - May Phu Pwint Wai; Amornchai Chaichana; Winai Jaikla; Surapong Siripongdee; Peerawut Suwanjan (International Journal of Power Electronics and Drive Systems/International Journal of Electrical and Computer Engineering, 2021)
This research paper contributes the one input three output voltage mode universal biquad filters with linear and electronic control of the natural frequency (w0), using two commercially available ICs, LT1228s as active device with two grounded capacitors, five resistors. The presented universal biquad filters can simultaneously provide three voltage-mode filtering functions, low-pass (LP), high-pass (HP) and band-pass (BP) without changing the circuit architecture. Furthermore, the first presented biquad filter provides low impedance at HP, BP voltage output nodes and LP, BP output voltage nodes are low impedance for the second proposed filter which is easy cascade ability with other voltage mode circuits without the employment of buffer circuits. The quality factor (Q) of both proposed filters is orthogonally adjusted from the passband voltage gain and w0. The proposed filters are simulated and experimented with commercially accessible ICs, LT1228. The simulated and experimental results demonstrate the filtering performances.
Keywords: Analog and Mixed-Signal Circuit Design; Power Quality and Harmonics; Advanced Adaptive Filtering Techniques